Hasil pendaftaran perusahaan/usaha Kabupaten Aceh Tenggara (Sensus ekonomi 1986., 1987)
Results of the 1986 economic census on corporate enterprises and home-based businesses in Kabupaten Aceh Tenggara, Propinsi Aceh.